Peran Pembelajaran Nahwu dan Sharf dalam Memahami Struktur Gramatikal Ayat-ayat Musykilat dalam Al-Qur'an - Nasrullah, M Alaika; Badriatul Jamroh , Nur Maya (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This research aims to analyze the role of Nahwu and Sharf learning in enhancing the understanding of tahfidz students regarding the grammatical structure of difficult verses in the Qur'an. The method used is qualitative with an intrinsic case study approach at UPT Bina Qurani, involving participant observation, in-depth interviews, and document analysis. The research results show that Nahwu-Sharf learning based on the context of musykilat verses increases grammatical understanding by 60%, especially in the analysis of complex structures such as isim maushul and fi'il mudhari'. The scaffolding approach (i'rab diagrams, collaborative discussions) has proven effective in reducing cognitive load, while the hierarchical curriculum design reinforces mastery of rare grammatical patterns. In conclusion, the integration of Nahwu-Sharf with direct analysis of the Quranic text is a fundamental solution to address the grammatical difficulties faced by tahfidz students, ensuring the accuracy of interpretation and practice of Islamic teachings.